The Role Of A Halcal Creed Teacher In Developing Emotional Intelligence Students At MTS Pab 4 Patumbak II - Nelsi Nelsi; Hotni Sari Harahap; Irwansyah Irwansyah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Emotional intelligence is the knowledge of self-knowledge, self-awareness, social sensitivity, empathy, and the ability to communicate effectively with others. Improving emotional intelligence is essential because it enables students to develop an awareness of how to manage their feelings, which then becomes a framework for behavior, socializing, and making informed decisions. However, to improve the emotional intelligence of students at MTs PAB 4 Patumbak II, a strategy of Akidah Akhlak teachers is needed. This study aims to determine the role of Akidah Akhlak teachers in developing the emotional intelligence of students at MTs PAB 4 Patumbak II and the level of emotional intelligence of students at MTs PAB 4 Patumbak II. This research is a qualitative descriptive research. The subjects of this study are teachers of the subject of aqidah akhlak, the data collection methods in this study are observation, interviews and documentation. Based on the results of the research that has been done the role of aqidah akhlak teachers in developing the emotional intelligence of students at MTs PAB 4 Patumbak II, namely: Teachers are able to understand the character of students, Teachers recognize the types of emotions of students, Provide guidance to students, Provide motivation in developing intelligence, emotional students, Development of emotional intelligence in Aqidah Akhlak lessons, and Giving punishment to students who violate the rules at school. The strategies used by Aqidah Akhlak teachers in developing the emotional intelligence of students include aspects of recognizing their own emotions, recognizing the emotions of others, building relationships with others, and motivating themselves. The level of emotional intelligence of students at MTs PAB 4 Patumbak II , namely: Some students have been able to manage their emotions well, are able to motivate themselves and are able to interact well. During the teaching and learning process, some students are motivated to study diligently so they can be smart like their friends, dare to express their opinions and understand differences of opinion with their friends, and are confident. Students also participate in extracurricular activities that connect them with other students who have the same interests , such as participating in religious or sports development activities. Students also communicate well with their teachers, both in the teaching and learning process and outside the classroom or school points.